The zakah understanding, level of income and facilities on zakah compliance towards muzakki on income compliance in Kelantan - Ab Rahman, Siti Maziah; Ab Rahman, Nurul Hidatah; Ahmad Tajuddin, Nur Hafizah; Mat Jusoh, Nor Asmira; Nik Din, Nik Muniyati; Mohd Zaki, Adeeba Najihah; 7 (Journal of Islamic, Social, Economics and Development, 2025)
Zakah income is one of the requirements that must be met and should not be overlooked by those who are eligible to pay. The purpose of this conceptual paper is to investigate the complicated dynamics that surround muzakki's compliance measures in terms of controlling and disclosing their income. Our goal is to build a complete framework that exposes the incentives, barriers, and potential methods for increasing voluntary compliance in this unique situation by drawing on existing research in Islamic finance, behavioural economics, and taxation studies. This research employs three sorts of variables to assess the study. Why don't some employees or companies satisfy their zakah responsibilities despite working? Questionnaires and other tests were administered using SPSS to determine the relationship between each element. Descriptive analysis, correlation, and regression are some of the methods used to draw findings and make recommendations for the study as well as future researchers. Zakah income is unquestionably one of the requirements that all Muslims must fulfil, which means that they should not ignore the obligation and should always learn about Shariah Compliance in order to increase positive compliance action in themselves. The study suggests various paths for future research to improve our theoretical model and provide practical recommendations for legislators, community leaders, and educational institutions seeking to achieve higher levels of income compliance among muzakki. These include forming collaborative collaborations with stakeholders, researching cutting-edge communication strategies, and leveraging technology to improve accountability and transparency. Finally, it is hoped that this effort will contribute to the development of a more resilient and long-lasting zakah administration system that better serves both donors and beneficiaries.